ChemInform Abstract: One‐Pot Construction of 3, 3′‐Bisindolylmethanes Through Bartoli Indole Synthesis. Issue 50 (10th December 2013) - Abe, Takumi; Nakamura, Shuuhei; Yanada, Reiko; Choshi, Tominari; Hibino, Satoshi; Ishikura, Minoru
Abstract The synthesis of a wide variety of bisindolylmethanes is achieved via reaction of nitromethanes with vinylmagnesium bromide, followed by quenching with HCl or reaction with aldehydes.